MECHANICAL DRAWING : applied on a manufacturing process in a metallurgical industry - Merlin Marcon, Fernando; Ronaldo (Revista Interface Tecnológica, 2022)
The mechanical technical design can be considered one of the fundamental factors in the production process, as it allows for improvements in communication and elaboration of the manufacturing process and the resulting quality. This article addresses the importance of using technical drawing in the manufacturing process. In this scenario, a brief survey was carried out on the historical evolution of the transition from freehand drawing to 2D and 3D software. In addition, the main concepts about the elements and characteristics of mechanical technical drawing are presented. Then, a case study is presented on the application of mechanical technical design in one of the production processes of a metallurgical company. The main results point to gains such as reduction of process time, inventory reduction and waste elimination.